(untitled) (International Journal of Ayurveda and Pharma Research, 2017)
Ayurveda is the science of life having wide description of Krimighna dravya in its literature. Ayurvedic pharmacopeia of India published by the Ministry of AYUSH is a monograph of single drugs; which is very popular for all stack holder of Ayush system of medicines. This article details the review of single drugs mentioned in API part I (Vol I to VI) and their screening for Krimighna (antimicrobial) properties. Present article also aims for validating classical fact with published scientific research work. Authors searched 54 drugs out of 519 single drugs described in the API & it was found most of Ayurvedic Krimighnadravya were recognized for having antimicrobial property which was established through various Preclinical & clinical work carried out by the scientific community. Authors collected data with references to validate API drugs having antimicrobial property. All screened content can be taken for various high-tech research work by various students in MD, PhD or in the various other project of CSIR, DST, EMR project of CCRAS for further development of new drugs and conversion of available drugs to latest dosage form.